Breaking the Language Barrier: Anxiety, Its Impacts, and Coping Mechanisms of Student Interpreters - Sabrina, Sabrina (Universitas Teuku Umar, 2025)
Interpreting has long been regarded as a challenging task as it requires heightened cognitive and emotional effort in real-time, and anxiety often affects the interpreting performance. This study explored the factors and impacts of anxiety on the interpreting skills of students who are prospective interpreters. Using a qualitative approach, the study conducted semi-structured interviews with 15 English Department students at Universitas Serambi Mekkah who had finished the interpreting examination. Data were analyzed using thematic analysis, and four-anxiety-inducing factors were identified: Fear of Making Mistakes (80%), Lack of Self-Confidence (66%), Time Pressure (66%), and Lack of Preparation (46.6%). The impacts involved performance-related issues, cognitive impairment, physical symptoms, impaired active listening and attention. To cope with the challenges, the student interpreters employed preparation-based approaches, practice and skill development, physical relaxation techniques, and social support systems. This research provides insights that, even though the students independently adopted their own coping mechanisms, interpreting trainers or instructors should also take part in reducing their anxiety, such as incorporating stress management techniques, frequent simulation exercises, and confidence-building activities that could better prepare them for real-world interpreting scenarios.